Healthcare providers' perspectives on use of the national guideline for family planning services in Amhara Region, Ethiopia: a qualitative study. Issue 2 (20th February 2019) - Tessema, Gizachew Assefa; Gomersall, Judith Streak; Laurence, Caroline O; Mahmood, Mohammad Afzal
Abstract : Objective: To explore healthcare providers' views on barriers to and facilitators of use of the national family planning (FP) guideline for FP services in Amhara Region, Ethiopia. Design: Qualitative study. Setting: Nine health facilities including two hospitals, five health centres and two health posts in Amhara Region, Northwest Ethiopia. Participants: Twenty-one healthcare providers working in the provision of FP services in Amhara Region. Primary and secondary outcome measures: Semistructured interviews were conducted to understand healthcare providers' views on barriers to and facilitators of the FP guideline use in the selected FP services. Results: While the healthcare providers' views point to a few facilitators that promote use of the guideline, more barriers were identified. The barriers included: lack of knowledge about the guideline's existence, purpose and quality, healthcare providers' personal religious beliefs, reliance on prior knowledge and tradition rather than protocols and guidelines, lack of availability or insufficient access to the guideline and inadequate training on how to use the guideline. Facilitators for the guideline use were ready access to the guideline, convenience and ease of implementation and incentives. Conclusions: While development of the guideline is an important initiative by the Ethiopian government for improving quality of care in FP services, continued use of this resource by all healthcare providers requires planning to promote facilitating factors and address barriers to use of the FP guideline. Training that includes a discussion about healthcare providers' beliefs and traditional practices as well as other factors that reduce guideline use and increasing the sufficient number of guideline copies available at the local level, as well as translation of the guideline into local language are important to support provision of quality care in FP services.